Unseasonable youth modernism, colonialism, and the fiction of development - Esty, Joshua, 1967- (New York : Oxford University Press, 2012)
'Unseasonable Youth' examines a range of modernist-era fictions that cast doubt on the ideology of progress through the figure of stunted or endless adolescence.
Description based on print version record.
Includes bibliographical references and index.
Keywords: English fiction -- 19th century -- History and criticism; English fiction -- 20th century -- History and criticism; Modernism (Literature) -- Great Britain; Bildungsromans, English -- History and criticism; Youth in literature; Adolescence in literature; Progress in literature; Colonies in literature; Imperialism in literature